Review of the genus Allochotes (Coleoptera: Cleridae: Neorthopleurinae) from Taiwan - Murakami, Hiroyuki; Yamasako, Junsuke; Chou, Wen-I; Yang, Ganyan (Zootaxa, 2013)
The Taiwanese species of the genus Allochotes are reviewed with descriptions of two new species, A. forniculatus sp. n. and A. piceus sp. n. A new synonymy is proposed: A. violaceipennis Schenkling syn. n. (= A. sauteri Schenkling). The Taiwanese Allochotes species are divided into three species groups based on the male genital structures.